El delito de persecución o acecho en el derecho alemán: postura del tribunal supremo (2020)
The crime of persecution of § 238 StGB was reformed by the Law of March 1st, 2017, ceasing to be a result crime to become a suitability crime. So that the author is no longer required to cause a serious disturbance in the way of life of the harassed person, but it is enough that his conduct is objectively adequate for it. However, a controversial analogical clause remains in section 1, number 5 of § 238 StGB. It has been labeled as unconstitutional for violating the principle of certainty, but the legislator has decided not to repeal it, in order to continue allowing the punishment of actions not expressly foreseen, but of similar severity.